1984
DOI: 10.1177/000992288402300707
|View full text |Cite
|
Sign up to set email alerts
|

Problems in the Clinical and Roentgenographic Diagnosis of Pneumonia in Young Children

Abstract: The difficulty of diagnosing pneumonia by chest x-ray in children less than 4 years of age was studied by comparing the chest roentgenograms of 34 healthy children with the chest roentgenograms of 34 children previously diagnosed as having pneumonia. Review of these films without knowledge of the previous interpretation and without clinical information disclosed variations regarding the roentgenographic confirmation of pneumonia in 24 percent of the cases and variations regarding the location of the lesion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…The proportion of agreement between the panel and the radiologists at Department of Radiology on a positive diagnosis was not satis factory, although affected by the relatively low number of pneumo nias. However, similar results were found in the study of STICKLER et al (10). Better agreement would probably have been obtained if follow-up films had been available for both.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The proportion of agreement between the panel and the radiologists at Department of Radiology on a positive diagnosis was not satis factory, although affected by the relatively low number of pneumo nias. However, similar results were found in the study of STICKLER et al (10). Better agreement would probably have been obtained if follow-up films had been available for both.…”
Section: Discussionsupporting
confidence: 83%
“…A noteworthy interobserver variability in the interpretation of chest radiographs (7), including the radiographie diagnosis of pneu monia in children (10), has been demonstrated. We assessed the diagnostic agreements on the diagnosis of pneumonia between the reports given by the specialist in radiology at the Department of Radiology, 3 independent interpreters, and a radiologie panel.…”
mentioning
confidence: 99%
“…Few prior studies have assessed the reliability of chest radiograph findings in children. 3,5,12,14,15 We found a high degree of agreement among radiologists for radiologic findings consistent with bacterial pneumonia when standardized interpretation criteria were applied. In this study, we identified radiographic features of pneumonia, such as alveolar infiltrate and pleural effusion, that were consistently identified by different radiologists reviewing the same radiograph and by the same radiologist reviewing the same radiograph.…”
Section: Discussionmentioning
confidence: 73%
“…As such, physicians in developed countries rely on chest radiography to establish the diagnosis of pneumonia. [1][2][3] However, there are limited data investigating the reliability of this test for the diagnosis of pneumonia in children. 2,[4][5][6] Prior investigations have noted poor overall agreement by emergency medicine, infectious diseases, and pulmonary medicine physicians, and even radiologists, in their interpretation of chest radiographs for the diagnosis of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation